Simulation and design of a three-stage metal hydride hydrogen compressor based on experimental thermodynamic data. (29th March 2018) - Galvis E, A.R.; Leardini, F.; Ares, J.R.; Cuevas, F.; Fernandez, J.F.
Abstract: A semi-empirical method was developed to design a three stage Metal Hydride Hydrogen Compressor (MHHC) through the determination of thermodynamic properties of several hydrides. As a first step, three AB2 -type alloys that satisfy operation conditions were selected from published thermodynamic data entailing over 200 single plateau hydrides. These alloys were synthetized by arc melting and characterized by X-Ray Powder Diffraction (XRPD), Scanning Electron Microscopy (SEM) and Energy Dispersion X-ray spectroscopy (EDX). Absorption and desorption Pressure-composition-Isotherms (P-c-I) were determined between 23 and 80 °C to characterize their thermodynamic properties. Subsequently, an algorithm that uses these experimental data and a real equation of state for gaseous H2 was implemented to simulate the volume, alloy mass, pressure and temperature of operation for each compressor stage, while optimizing the compression ratio and total number of compressed H2 moles. Optimal desorption temperatures for the three stages were identified within the range of 110–132 °C. A system compression ratio (CR) of 92 was achieved. The number of H2 moles compressed, the alloy mass and volume of each stage depend linearly on the volume of the external tank in which the hydrogen is delivered. Highlights: A methodology is implemented to design a three stage metal hydride compressor. Three AB2 compounds have been selected from literature thermodynamic data. The model determines the best temperature, alloy mass and volume at each stage. H2 moles compressed depends on the reversible capacity and desorption pressure. The real thermodynamics of hydrides affect importantly the compressor design.